Tectonic context of moderate to large historical earthquakes in the lesser Antilles and mechanical coupling with volcanoes - Feuillet, Nathalie (2012)
The oblique convergence between North American and Caribbean plates is accommodated in a bookshelf faulting manner by active, oblique-normal faults in the northern part of the Lesser Antilles arc. In the last 20 years, two M > 6 earthquakes occurred along a large, arc parallel, en echelon fault system, the 16 March 1985 in Redonda and 21 November 2004 in Les Saintes. A better understanding of active faulting in this region permit us to review the location and magnitude of historical earthquakes by using a regional seismic attenuation law. Several others moderate earthquakes may have occurred along the en echelon fault system implying a strong seismic hazard along the arc. These faults control the effusion of volcanic products and some earthquakes seem to be correlated in time with volcanic unrest. Shallow earthquakes on intraplate faults induced normal stress and pressure changes around neighboring volcano and may have triggered volcanic activity. The Redonda earthquake could have initiated the 1995 eruption of Montserrat's Soufrière Hills by compressing its plumbing system. Conversely, pressure changes under the volcano increased Coulomb stress changes and brought some faults closer to failure, promoting seismicity. We also discuss the magnitude of the largest 11 January 1839 and 8 February 1843 megathrust interplate earthquakes. We calculate that they have increased the stress on some overriding intraplate faults and the extensional strain beneath several volcanoes. This may explain an increase of volcanic and seismic activity in the second half of the 19th century culminating with the devastating, 1902 Mount Pelée eruption.